Transformasi Manajemen Keberlanjuan melalui Teknologi Hijau: Membangun Keunggulan Kompetitif - Evita Kusumawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In the era of globalization and increasingly pressing climate change, sustainability management has become a central issue in business strategy. Transforming sustainability management through green technology serves not only to fulfill corporate social responsibility but also as a tool for building competitive advantage. This study aims to explore how green technology can be integrated into sustainability management and its impact on organizational performance. Through a literature analysis approach, this study identifies various green technologies that have been adopted by companies in various sectors, including agriculture, renewable energy, and waste management. Data shows that implementing green technology can improve operational efficiency, reduce costs, and improve a company's image in the eyes of consumers. In the agricultural sector, the use of information and communication technology has been shown to increase productivity and sustainability. The use of artificial intelligence in management information systems can improve the sustainable performance of small and medium enterprises (SMEs). Thus, green technology contributes not only to environmental sustainability but also to sustainable economic growth. This study also includes an analysis of the challenges faced in implementing green technology, including high initial costs and a lack of knowledge among business actors. However, the long-term benefits of investing in green technology, such as reduced carbon emissions and enhanced brand reputation, far outweigh the costs. Therefore, transforming sustainability management through green technology is a strategic option that companies seeking to remain competitive in the global marketplace cannot ignore.